Old Testament Origins and the Question of God - Bartholomew, Craig G. (Bulletin for biblical research, 2017)
This article begins with an examination of the worldview and the view of history embodied in Ps 93. Psalm 93 encapsulates a view of history with Yahweh at the center and that can be summed up as “Yahweh reigns.” This is connected with holistic readings of the psalms that see them as a whole articulating a theology of the kingdom of God. On this basis, the possibility of the OT presenting a unique view of history is explored and affirmed, albeit one that developed over time. I argue that scholars who confess Ps 93 should embrace this view of history in their scholarly work, and I explore the implications of this for historical criticism and for the historicity of Moses. I recognize, in conclusion, that major work remains to be done in revisiting OT origins in light of the question of God.